2010
DOI: 10.1590/s0036-46652010000400006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimalarial activity and cytotoxicity of some selected cuban medicinal plants

Abstract: SUMMARYTerrestrial plants have been demonstrated to be sources of antimalarial compounds. In Cuba, little is known about antimalarial potentials of plant species used as medicinals. For that reason, we evaluated the antimalarial activity of 14 plant species used in Cuba as antimalarial, antipyretic and/or antiparasitic. Hydroalcoholic extracts were prepared and tested in vitro for the antimalarial activity against Plasmodium falciparum Ghana strain and over human cell line MRC-5 to determine cytotoxicity. Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
(27 reference statements)
2
35
0
2
Order By: Relevance
“…Corroborating the data found in this study, Valdés et al (2010) confirmed the presence of quinones, phenols, triterpenes, lactonic compounds, alkaloids, steroids, amino acids, saponins and flavonoids.…”
Section: Phytochemical Analysissupporting
confidence: 88%
“…Corroborating the data found in this study, Valdés et al (2010) confirmed the presence of quinones, phenols, triterpenes, lactonic compounds, alkaloids, steroids, amino acids, saponins and flavonoids.…”
Section: Phytochemical Analysissupporting
confidence: 88%
“…Isolation of 4-phenylpropanoids from Australian species of C. ambiguus has been reported. These compounds are eugenol (4-allyl-2-methoxyphenol) (18); elemicin (5-allyl-1,2,3-trimethoxybenzene) (19); eugenol methylether (4-allyl-1,2-dimethoxybenzene) (20) and trans-iso-elemicin (1,2,3-trimethoxy-5-(1-propenyl) benzene) (21) and all these isolates exhibited good inhibition activity against ADP-induced human platelet serotonin release which is associated with headaches [26].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In herbal medicine, S. jamaicensis itself has been known to demonstrate antacid, analgesic [13], anti-inflammatory [12], hypotensive [3], antihelminthic [14], diuretic, laxative, lactagogue, purgative, sedative, spasmogenic, vasodilator, vulnerary, and vermifuge properties [1, 8, 15]. …”
Section: Traditional Usage Of Stachytarpheta Jamaicensismentioning
confidence: 99%